FACTORS AFFECTING TAX AGGRESSIVENESS WITH MODERATION OF EARNINGS MANAGEMENT - Rombe, Eunike Immaculata; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to acquire the empirical evidences from the factors affecting tax aggressiveness with moderation of earnings management. Total sample data were 165 from 55 manufacturing companies listed on Indonesia Stock Exchange (IDX) for the period of 2018-2020. Purposive sampling was used in this research. The hypothesis testing method in this research was done by using the moderated regression analysis model which was processed with EViews 12 SV software. Fixed effect model (FEM) was the suitable model in this research. Tax aggressiveness is proxied by effective tax rate (ETR). The result shows that ROA, DER, firm size, and CIR have no significant effect on ETR. Earnings management also could not moderate the effect of ROA, DER, firm size, and CIR on tax aggressiveness.